Nanoscale perfluorocarbon expediates bone fracture healing through selectively activating osteoblastic differentiation and functions - Shunhao Wang; Jiahuang Qiu; Anyi Guo; Ruanzhong Ren; Wei He; Sijin Liu; Yajun Liu (Journal of Nanobiotechnology, 2020)
Abstract Background and rationale Fracture incidence increases with ageing and other contingencies. However, the strategy of accelerating fracture repair in clinical therapeutics remain a huge challenge due to its complexity and a long-lasting period. The emergence of nano-based drug delivery systems provides a highly efficient, targeted and controllable drug release at the diseased site. Thus far, fairly limited studies have been carried out using nanomedicines for the bone repair applications. Perfluorocarbon (PFC), FDA-approved clinical drug, is received increasing attention in nanomedicine due to its favorable chemical and biologic inertness, great biocompatibility, high oxygen affinity and serum-resistant capability. In the premise, the purpose of the current study is to prepare nano-sized PFC materials and to evaluate their advisable effects on promoting bone fracture repair. Results Our data unveiled that nano-PFC significantly enhanced the fracture repair in the rabbit model with radial fractures, as evidenced by increased soft callus formation, collagen synthesis and accumulation of beneficial cytokines (e.g., vascular endothelial growth factor (VEGF), matrix metalloprotein 9 (MMP-9) and osteocalcin). Mechanistic studies unraveled that nano-PFC functioned to target osteoblasts by stimulating their differentiation and activities in bone formation, leading to accelerated bone remodeling in the fractured zones. Otherwise, osteoclasts were not affected upon nano-PFC treatment, ruling out the potential target of nano-PFC on osteoclasts and their progenitors. Conclusions These results suggest that nano-PFC provides a potential perspective for selectively targeting osteoblast cell and facilitating callus generation. This study opens up a new avenue for nano-PFC as a promising agent in therapeutics to shorten healing time in treating bone fracture.